HUBUNGAN ASUPAN MAKAN DAN POLA ASUH DALAM PEMBERIAN MAKAN TERHADAP STATUS GIZI PADA BALITA UMUR 4-5 TAHUN - Rahmiati -; Luluk Yuliati (Jurnal Maternitas Kebidanan, 2023)
Nutritional status in toddlers can be influenced by food intake and parenting patterns in feeding. Food intake and parenting are indirect factors that are closely related to the nutritional status of children under five. The purpose of this study was to determine the relationship between food intake and parenting style in feeding the nutritional status of toddlers aged 4-5 years in the Sumbe village Namblong District, Jayapura Regency. The type of research used is correlational analytic approach cross sectional. The population is toddlers aged 4-5 years, the sampling technique used is purposive sampling, with a sample of 30 toddlers. The results showed that most of the toddlers (73,3%) had sufficient food intake; more mothers who have democratic parenting style in providing food (63,3%); and the majority of toddlers have good nutritional status (76,7%). There is a positive and statistically significant relationship between food intake and nutritional status (ρ=0,529 and p= 0,003), and there is a positive and statistically significant relationship between parenting style in feeding and nutritional status of toddlers (ρ=0,566 and p=0,001). The better the food intake and parenting style in feeding that is applied, the better the nutritional status of toddlers.